2016
DOI: 10.1177/2211068215601612
|View full text |Cite
|
Sign up to set email alerts
|

Development and Implementation of Autoverification Rules for ELISA Results of HBV Serological Markers

Abstract: Autoverification is a process of using computer-based rules to verify clinical laboratory test results without manual review. But to date, there are few published articles on the use of autoverification over the course of years in a clinical laboratory. In our study, we firstly described the development and implementation of autoverification rules for enzyme-linked immunosorbent assay (ELISA) results of hepatitis B virus (HBV) serological markers in a clinical immunology laboratory. We designed the autoverific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 59 publications
(83 reference statements)
0
13
0
Order By: Relevance
“…Although other studies have been reported on autoverification practices with respect to other commonly run tests in the clinical laboratory, including hepatitis B virus ELISAs,[7] thyroid function profiles,[8] as well as for clinical chemistry panels,[910] we are only aware of two other papers discussing autoverification for coagulation applications. [1112] In the papers focusing on coagulation applications, autoverification practices are featured with regard to routine coagulation parameters, including prothrombin time (PT), aPTT, and fibrinogen[12] and PT, aPTT, fibrinogen, D-dimer, and AT.…”
Section: Resultsmentioning
confidence: 99%
“…Although other studies have been reported on autoverification practices with respect to other commonly run tests in the clinical laboratory, including hepatitis B virus ELISAs,[7] thyroid function profiles,[8] as well as for clinical chemistry panels,[910] we are only aware of two other papers discussing autoverification for coagulation applications. [1112] In the papers focusing on coagulation applications, autoverification practices are featured with regard to routine coagulation parameters, including prothrombin time (PT), aPTT, and fibrinogen[12] and PT, aPTT, fibrinogen, D-dimer, and AT.…”
Section: Resultsmentioning
confidence: 99%
“…At present, the most common methods of virus testing in clinical laboratory settings include as following: serological diagnosis based on antigen or antibody such as ELISA [2][3][4], and nucleic acid test methods including PCR [5], RT-PCR [6,7], real-time PCR [8][9][10][11][12][13], and molecular hybridization [14][15][16], etc. However, there may be different test results when different kits or test methods were used.…”
Section: Discussionmentioning
confidence: 99%
“…The most common method of determining the concentration of immune complexes is the ELISA test. However, it demands a set of enzymes, markers, and reagents so it is currently impossible to implement it for regular screening of the 2 of 13 population [6,7]. The opposite disadvantages belong to hemolytic tests, used to assess the activity of the immune system in general.…”
Section: Introductionmentioning
confidence: 99%